IMPLEMENTATION OF CRYPTOGRAPHY AND STEGANOGRAPHY FOR TEXT ON COVER IMAGE USING AES AND F5 ALGORITHM - Ratna Astuti Nugrahaeni; R. Rumani M. R. Rumani M.; Surya Michrandi Nasution (TEKTRIKA, 2016)
This journal explains about implementation that combine both cryptography and steganography method for texton cover image to increase the security level. Text will be encrypted with AES algorithm, and then it will be embedded to the cover image using F5 algorithm. The implemented AES algorithm has a good performance, with Avalanche Effect value ranges from 0.43 – 0.59. The resulting image, or stego image, has a very similar histogram with the original image, so there is no significant difference between the two of them. However, the file size change about 1.25 – 3.25 times larger than theoriginal image. If noise or disruption is given to stego image, the information can not be extracted.Keywords: cryptography, steganography, AES, F5